Civil-Legal Relations on Land are Being Improved in Uzbekistan - Zhumayevich, Kholmuminov Oybek (European Journal of Life Safety and Stability (2660-9630), 2021)
the article analyzes the new civil-legal norms of land relations in the country, its legal basis, theoretical and practical aspects of Appeals issued by the population, as well as offers on the establishment of land relations and their consideration by the Republican and regional councils and puts forward their comments on land relations in Uzbekistan.